From free-fermionic constructions to orbifolds and back - Ioannis Florakis; John Rizos (Journal of High Energy Physics, 2024)
Abstract We systematically develop the explicit map between string vacua constructed in the Free Fermionic Formulation and their ℤ 2 N $$ {\mathbb{Z}}_2^N $$ toroidal orbifold counterparts. We illustrate the map in various example classes of models, including cases relevant for string phenomenology, as well as in theories where space-time supersymmetry is broken by the stringy Scherk-Schwarz mechanism.